2021
DOI: 10.1021/acs.jafc.1c02616
|View full text |Cite
|
Sign up to set email alerts
|

Structure Simplification of Natural Products as a Lead Generation Approach in Agrochemical Discovery

Abstract: Natural products (NPs) have a long history as sources of compounds for crop protection. Perhaps a more important role for NPs has been as models and inspiration for the discovery and development of synthetic crop protection compounds. NPs and their synthetic mimics account for 18% of all crop protection compounds, whereas another 38% of all crop protection compounds have a NP that could have served as a model. Because NPs are often complex molecules, have limited availability, or possess structural features th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 174 publications
1
103
0
Order By: Relevance
“…In 1 H-NMR spectra, multiplet signals at δ 7.35 -6.37 ppm indicated the presence of protons in aromatic nucleuses, and a singlet at δ 4.15 -2.17 ppm revealed the presence of -SÀ CH 2 -, -OÀ CH 2 -and -OCH 3 characteristic groups. The 13 C-NMR spectrum of E1 confirmed the presence of C=O and -CH 2 -groups at 173.86 ppm and 30.13 -28.75 ppm in the 13 C-NMR spectrum. The HR-MS spectra of target compounds revealed that absorption signals of [M + H] + ions was consistent with its molecular weight.…”
Section: Chemistrymentioning
confidence: 65%
See 2 more Smart Citations
“…In 1 H-NMR spectra, multiplet signals at δ 7.35 -6.37 ppm indicated the presence of protons in aromatic nucleuses, and a singlet at δ 4.15 -2.17 ppm revealed the presence of -SÀ CH 2 -, -OÀ CH 2 -and -OCH 3 characteristic groups. The 13 C-NMR spectrum of E1 confirmed the presence of C=O and -CH 2 -groups at 173.86 ppm and 30.13 -28.75 ppm in the 13 C-NMR spectrum. The HR-MS spectra of target compounds revealed that absorption signals of [M + H] + ions was consistent with its molecular weight.…”
Section: Chemistrymentioning
confidence: 65%
“…A micro thermophoresis instrument was used to research the interaction between TMV-CP and the compounds (NanoTemper Technologies GmbH, Germany). A 400 NMR spectrometer was used to obtain 1 H, 13 C and 19 F NMR spectra (Bruker Optics, Switzerland). The X-4B melting point instrument was used to obtain melting point data (Shanghai INESA Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…49 2.2 Natural products with new modes of action as lead compounds and target site identification Natural products have been a source of new chemistries and new MOAs for pesticides, including herbicides. 50,51 Of commercial herbicides, natural products, modified natural products (e.g. semisynthesis), and natural product mimics (purely synthetic) account for about 15% of the MOAs of commercial herbicides, but another 35% of these MOAs could have been derived from research with natural phytotoxins.…”
Section: Discovery Approachesmentioning
confidence: 99%
“…Natural products have been a source of new chemistries and new MOAs for pesticides, including herbicides 50,51 . Of commercial herbicides, natural products, modified natural products (e.g.…”
Section: Discovery Approachesmentioning
confidence: 99%